Cold Baryogenesis from first principles in the two-Higgs doublet model with fermions - Mou, Zong-Gang; Saffin, Paul M.; Tranberg, Anders (Springer, 2015)
We present a first-principles numerical computation of the baryon asymmetry in electroweak-scale baryogenesis. For the scenario of Cold Baryogenesis, we consider a one fermion-family reduced CP-violating two Higgs-doublet model, including a classical SU(2)-gauge/two-Higgs sector coupled to one quantum left-handed fermion doublet and two right-handed singlets. Separately, the C(CP) breaking of the two-Higgs potential and the C and P breaking of the gauge-fermion interactions do not provide a baryon asymmetry. Only when combined does baryogenesis occur. Through large-scale computer simulations, we compute the asymmetry for one particularly favourable scalar potential. The numerical signal is at the boundary of what is numerically discernible with the available computer resources, but we tentatively find an asymmetry of |η|≤3.5×10−7.